Calcitriol sensitizes colon cancer cells to H2O2-induced cytotoxicity while inhibiting caspase activation - Koren, Ruth; Wacksberg, Shiri; Weitsman, Gregory E.; Ravid, Amiram (Econometrica, 2006)
The anti-cancer activity of calcitriol, the active metabolite of Vitamin D, in the colon is usually attributed to its anti-proliferative and pro-differentiative actions. The levels of reactive oxygen species (ROS) are high in colon carcinomas due to increased aerobic metabolism and exposure to various anti-cancer modalities. We examined whether calcitriol modulates the response of colon cancer cells to the cytotoxic action of the common mediator of ROS injury, H2O2. Pretreatment with calcitriol (100 nM, 48 h) sensitized HT-29 colon cancer cells to cell death induced by acute exposure to H2O2 or chronic exposure to the H2O2 generating system, glucose/glucose-oxidase. Although the morphological features of H2O2-induced HT-29 cell death are consistent with apoptosis, we detected no executioner caspase activation in response to cytotoxic concentrations of H2O2 and treatment with a pan-caspase inhibitor did not affect H2O2-induced cytotoxicity nor its enhancement by calcitriol. Conversely, exposure of HT-29 cells to sub-toxic concentrations of H2O2 resulted in low executioner caspase activation that was inhibited by pretreatment with calcitriol. The sensitization of colon cancer cells to ROS-induced cytotoxicity may contribute to its assumed action as a chemopreventive agent and to its therapeutic potential alone or in combination with other anti-cancer modalities.